Pengaruh Penggunaan Media Canva terhadap Kemampuan Menulis Teks Negosiasi Siswa Kelas X SMA - Sinaga, Audy Silvana Br; Simaremare, Juni Agus; Sitorus, Pontas J. (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This research aims to determine the effect of using Canva media as a means of delivering material on students' ability to write negotiation texts. This is motivated by students' low writing skills, especially in negotiation text material.Method – This research uses a quantitative experimental method, namely the method used to find out how the independent variable, or in this research the use of Canva media influences the dependent variable, namely the student's ability to write negotiation texts. The population in this study was all class The data collection technique used is an assignment test to determine students' ability to write negotiation texts.Findings – The results of this research obtained an average of 78.78 for the experimental class and 66.12 for the control class. The results of the data requirements test show that the data for both classes are normally distributed and homogeneous. In the t-test, tcount > ttable = 6.3618 > 1.6698. Thus, it can be concluded that there was a significant effect of using Canva media on the ability to write student negotiation texts. Research Implications – This research proves that learning media is one of the important aspects of the success of teaching and learning activities. Interesting learning media will make it easier for teachers to convey material and students can also more easily understand and master learning. The Canva Application media which can stimulate images, and videos can make it easier for students to understand the material in searching for information and topics in written material, besides this, students play a more active role in learning activities to write negotiation texts.